Konsep Waktu Menurut Yusuf Qardhawi; Perspektif Semantik Leksikal - Mitrajati, Kenyo; Musthofa, Tulus; Nasiruddin, Nasiruddin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research discusses the importance of time written in the Al-Qur'an and Hadith as well as the views of ulama. This research is descriptive qualitative research that explores literature sources that are related to the research problem. This research uses a lexical semantic perspective. The research data is in the form of the term "time" with sources from the Al-Qur'an, Hadith, the book Al-Ḥayyāh fī al-Muslīm by Yusuf Qardhawi, and several literature. Data collection techniques are carried out using documentation. Meanwhile, data analysis uses content analysis. The results of the research show that there are four concepts related to the importance of time, namely: time terminology in the Al-Qur'an, characteristics of time, highlighting the importance of time in the Al-Qur'an, the Hadith of the Prophet, and among ulama, as well as explaining the obligations of Muslims towards time.